Implementasi Kegiatan Ekstrakurikuler Palang Merah Remaja Dalam Pembentukan Karakter Peduli Sosial Siswa - Usiono Usiono; Haniatul Khoiriyah; Dinda May Sarah; Mayang Sari Sipahutar; Annisa Inda Vika (Fakultas Tarbiyah IAI Nasional Laa Roiba, 2023)
The purpose of this research is to find out more about the character of students who participate in extracurricular activities of the Youth Red Cross. Besides that, the factors that influence the formation of the character of students participating in the Youth Red Cross extracurricular. This research is qualitative and descriptive in nature. This study used several subject teachers and student staff who were considered to have known PMR as samples. The core administrators, coordinators, and active members are PMR administrators. Observations, interviews, and documentation are used as data collection methods. On the other hand, primary and secondary data are the source of this research data. Keywords; Social skills, character development and PMR